Reconstruction of Extensive Soft-Tissue Defects with Concomitant Bone Defects in the Lower Extremity with the Latissimus Dorsi-Serratus Anterior-Rib Free Flap - Sia, Wei Tee; Xu, Germaine Guiqin; Puhaindran, Mark Edward; Tan, Bien Keem; Cheng, Mathew Hern Wang; Chew, Winston Yoon Chong (Journal of Reconstructive Microsurgery, 2015)
Background The combined latissimus dorsi-serratus anterior-rib (LD-SA-rib) free flap provides a large soft-tissue flap with a vascularized bone flap through a solitary vascular pedicle in a one-stage reconstruction.Methods Seven LD-SA-rib free flaps were performed in seven patients to reconstruct concomitant bone and extensive soft-tissue defects in the lower extremity (tibia, five; femur, one; foot, one). The patients were all male, with an average age of 34 years (range, 20–48 years). These defects were secondary to trauma in five patients and posttraumatic osteomyelitis in two patients.Results All flaps survived and achieved bony union. The average time to bony union was 9.4 months. Bone hypertrophy of at least 20% occurred in all flaps. All patients achieved full weight-bearing ambulation without aid at an average duration of 23.7 months. Two patients developed stress fractures of the rib flap. There was no significant donor site morbidity, except for two patients who had pleural tears during harvesting of the flap.Conclusion The LD-SA-rib flap provides a large soft-tissue component and a vascularized bone flap for reconstruction of composite large soft-tissue defects with concomitant bone defects of the lower extremity in a one-stage procedure.
Keywords: latissimus dorsi; vascularized rib; large soft tissue defect; lower extremity